Entrepreneurial orientation, performance of SMEs and moderating effect of microfinance in Nigeria - Zannah, Mohammed (2017)
This study examined the relationship between entrepreneurial orientation (innovation, risk taking and proactiveness) and SMEs Performance. Lack of research has been conducted on the entrepreneurial orientation in Nigeria. In addition, this study used microfinance facilities awareness, perception and acceptance as a Moderator. The study used existing theories of Research Based View and Expectancy Utility, incorporating various resources, internal and external factors that are leading to enterprises performance. The methodology used in this study is quantitative, three hundred and forty (340) questionnaires were distributed and 308 were successfully retrieved using simple random sampling and analysed to answer the research objective, descriptive analysis, correlation, multiple linear regression and hierarchical multiple regression were conducted to determine the relationship between innovation, risk taking, proactiveness, microfinance awareness, perception, acceptance and SMEs Performance Moderating effect of microfinance. Based on the six (6) hypothesis proposed, and analysed using correctional and regression analysis Microfinance awareness, perception and acceptance and entrepreneurial orientation has significant and positive relation with SMEs performance. The finding confirmed innovation and proactiveness are predictor of SMEs performance. Moreover based on the impact of the three moderator variables analysed by hierarchical regression on the relationship between entrepreneurial orientation and SMEs performance, it has been supported that risk taking and SMEs performance are moderated by all the moderator while proactiveness by only perception of Microfinance. None of the moderator change the relationship between innovativeness and SMEs performance. H1, H3, H4b, H5b, H5c, and H6c are supported. Therefore managers should consider microfinance facilities to moderate risk taking and proactiveness to SMEs performance. In conclusion, these findings would enable the academicians, government agencies and practitioners to focus on entrepreneur orientation in enhancing SMEs performance and also role of the microfinance facilities.